NATURAL RESOURCES PROTECTION STRATEGIES IMPORTANT FOR AGRICULTURE IN THE INTERNATIONAL COMMUNITY AND REPUBLIC OF SERBIA - Slobodan Nešković; Verica Savić Savić (Ekonomika Poljoprivrede (1979), 2018)
Agriculture as an economic activity depends heavily on living organisms and ecosystems for its vulnerability of nature and therefore the environment has become a common global problems of the modern world. International legislation in the feld of environmental protection has not yet reached the level that would allow a peaceful life for all people and all living creatures on our planet. During this research various methods of scientifc research were used in the breakdown of complex categories, methods of specialization and after synthesis elaboration, different conclusions were formed. On the basis of the aim of this paper, the methods are chosen which by their combination enable the quality realization of the research.